(untitled) (Journal of Global Humanities and Social Sciences, 2024)
In the context of the new era, the integration of smart sports and traditional martial arts has broad prospects for development. This article first explores the application scope of smart sports technology in martial arts training and demonstrates its significant effect in improving training efficiency and accuracy through case analysis. Then, the practical significance of the integration of smart sports and traditional martial arts was analyzed, including promoting the modern inheritance of traditional culture, improving training effects and popularity, reducing the risk of injury, and its application value in the fields of health management and rehabilitation therapy. On this basis, specific strategies for the integrated development of smart sports and traditional martial arts in the new era are proposed, including promoting the popularization and application of smart sports technology; building a scientific and efficient education and training system to cultivate compound talents; strengthening technology companies and martial arts experts cooperation to jointly develop intelligent equipment and systems suitable for martial arts training. These practices aim to provide new paths and impetus for the integrated development of smart sports and traditional martial arts and promote the modern inheritance and innovative development of Chinese traditional culture.